KONDISI PROGRAM STUDI PENDIDIKAN MATEMATIKA DITINJAU DARI JUMLAH PEMINATNYA - AMINULLAH AMINULLAH (GANEC SWARA, 2022)
The purpose of this study is to describe the condition of the mathematics education study program in terms of the number of enthusiasts. The type of research used is literature review research with a descriptive quantitative approach. The data studied in the form of data on the number of students in the mathematics education study program for the last 5 years obtained/derived from national data on the government website (Kemdikbud), namely at https://pddikti.kemdikbud.go.id/.The results of the study show that public interest in the Mathematics Education Study Program at State Universities (PTN) and Private Universities (PTS) is different. The difference in interest can be seen in the increasing number of new students every year from 2017 to 2021. The addition of students at UNRAM starts from 30 to 191 students and UIN starts from -21 to 43 students. While at UNDIKMA the number of additional students experienced an increasing number of successively from 17, 46, 15, 28 and finally in 2021 as many as 17, as well as the addition of students at UMMAT in a row starting from -9, -7, 1, 9 and the last in 2021 as many as 5 students. So, the number of enthusiasts for the Mathematics Education Study Program is generally low and even lower in private uni versities